Cultivo de Scenedesmus acuminatus em água de maceração do milho e extração e quantificação de lipídeos - Tomas, Cristiane (2016)
The search for renewable energy sources is a concern of the new generations in face of possible fossil fuel scarcity and climate change caused by greenhouse gas emissions. When compared with diesel derived from petroleum, the biodiesel can reduce 78% carbon dioxide emissions, considering plants reabsorption; also, it can reduce by 90% emissions of smoke and virtu ally eliminates sulfur oxide. The purpose of this research was to investigate the cultivation of microalgae Scenedesmus acuminatus in the substrate composed by corn steep liquor for biodiesel production purposes. Initially a preliminary test was carried out to verify the viability of growing the microalgae in the effluent; further, a central composite design was carried to study the influence of the effluent and inoculum concentration on the cell density biomass, production of biomass, chemical oxygen demand (COD) and maximum growth rate (μmax) of microalgae culture. Statistical analysis indicated that the percentage of inoculum and effluent had na influence on the cell density, COD and maximum specific growth rate and that the optimal cultivation conditions would be achieved with the use of 53.5 % of efluente and 5.2% of inoculum. The proposed model was validated through cultivation under the proposed conditions, achieving 0.30 g/L of dry biomass on the seventh day. The cultivation, together with the coagulation procedure, was efficient for the removal of organic matter, verified through the COD and pH reduction, reaching the appropriate level according the standard required by current legislation. HARA & RADIN (1978) was more efficient for extraction at 45ºC: achieved a yield of 44,50 ± 2,12 mg / L total lipids. The extraction temperature had influence on the yield of lipids: the procedure performed at 45 ° C was able to extract more lipids in both methods.